Società civile e democrazia radicale - Cini, Lorenzo (Strumenti per la didattica e la ricerca, 2012)
This work asks questions on the relationship between innovative collective actors, such as the 'new social movements' and the political institutions of representative democracy starting from an underlying hypothesis: the idea that civil society is the main source of political legitimation of liberal democracy. More precisely, what this monograph reflects on is the capacity of the social movements to concretely test alternative forms of democracy. The aim of the contemporary movements is to augment the fundamental values of the "democratic revolution", namely the principles of freedom and equality. They constantly lead to conflict and social antagonism: indeed new conflicts and new antagonisms arise every time that the movements implement radical experiences of democracy in the multiple and different spheres of social life. Only by accepting and setting value by these alternative democratic practices and experiences - and this is the author of this work's thesis - may democratic ideals be revived in contemporary society.